Validated RP-HPLC-UV method for the determination of betulin in Asteracantha longifolia (L.) Nees. extract - Amal K. Maji; Niladri Maity; Pratim Banerji; Debdulal Banerjee (International Journal of Phytomedicine, 2013)
Asteracantha longifolia (L.) Nees. (Acanthaceae) is a well known medicinal plant of Indian traditional medicines. The aim of this work was to develop a validated reversed phase-high performance liquid chromatography (RP-HPLC) method for the quantitative determination of betulin in A. longifolia extract. The analysis was performed by RP-HPLC on Luna C18 (2) 100 Å, 250 x 4.6 mm column under isocratic elution of acetonitrile and water (80:20, v/v) with a flow rate of 1.0 ml/min and the total run time was 20 min. The column temperature was adjusted at 25°C and the detection wavelength was set at 210 nm. The method was validated for suitability, specificity, accuracy, precision, limits of detection and quantification (LOD and LOQ), robustness and ruggedness. The betulin content in A. longifolia extract was found to be 15.96 ± 0.34% (w/w). The calibration curve was linear over a concentration range of 10-125 μg/ml (r2 = 0.997) and the recovery range was 98.29-99.59%. The LOD and LOQ were 1.11 and 7.35 μg/ml, respectively. The intra- and inter-day assay precisions were satisfactory and the relative standard deviations were found to be always less than 2%. The developed method was found to be simple, sensitive, accurate, robust and rugged for the quantification of betulin. This validated method can be useful for the routine quality control analysis of betulin content in A. longifolia extract and its formulations.